Solve the system using elimination.

*i.)* `3x - 2y = 2`

*ii.)* `5x - 5y = 10`

Since equation *ii)* can be simplified by dividing every term by 5 this gives:

ii.) `x - y = 2`

Multiply equation `ii.)` by -2 to get:

`-2 (x - y = 2)...

## See

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

Solve the system using elimination.

*i.)* `3x - 2y = 2`

*ii.)* `5x - 5y = 10`

Since equation *ii)* can be simplified by dividing every term by 5 this gives:

ii.) `x - y = 2`

Multiply equation `ii.)` by -2 to get:

`-2 (x - y = 2) => -2x + 2y = -4`

Now add equation i.) and ii.) together:

`3x - 2y = 2`

`-2x + 2y = -4`

This gives: `x = -2`

Substitute x = -2 into one of the original equations to find y.

`3x - 2y = 2`

`3(-2) - 2y = 2`

`-6 - 2y = 2`

`-2y = 8`

`y = -4`

**The solution to the system is (-2, -4).**